Discharge Modelling of the Tungnaá River in Iceland using the HYPE Model - Sidney Marschollek 1993- (2017)
Hydropower plants produce the largest amount of electric energy in Iceland. The rivers with the largest energy potential and installed capacity are strongly influenced by seasonal variation due to additional water input by seasonal snow and glacier melting. In order to provide efficient energy production and maintain energy security, reservoir management and thus river discharge analysis is of great importance. This study investigates the accuracy of accumulated spring discharge simulation using the rainfall-runoff model HYPE for the Tungnaá catchment in Iceland. The model has been trained during a time period of 22 years using forcing data of the meteorological model HARMONIE and field measurements of discharge at the catchment outlet. Starting with a simple model setup which contained only fundamental processes, further model functions and modules where added to test the model’s capability of simulating monthly accumulated discharge. The results show that the model accuracy could be improved by adding modules dealing with groundwater and return-water flow and additionally with enhanced snow melting. A calibration of only the first 6 months of the year resulted in the best performing model setup for the spring period. While there is potential for further improvements of this modelling approach this study shows already potential for further development and for coupling with a weather forecasting model for discharge prediction. Stærsti hluti raforku á Íslandi er framleidd með vatnsaflsvirkjunum. Vatnsföll með mestu orkugetuna og uppsett afl eru háðar árstíðabundnum sveiflum á rennsli og því er skilvirk framleiðsla og orkuöryggi háð góðum spám um ómiðlað innrennsli til að tryggja skilvirkan rekstur lóna. Í þessari rannsókn er nákvæmni uppsafnaðs rennslis spáð með forritinu HYPE fyrir vatnasvið Tungnaá á Íslandi. Notuð eru 22 ár til að þjálfa líkanið með HARMONIE veðurlíkaninu ásamt raungögnum af rennsli af vatnasviðinu. Notkun HYPE líkansins til framtíðarspáa er prófað með því að skilgreina fyrst einfalda ...